1974
DOI: 10.1002/pol.1974.170120514
|View full text |Cite
|
Sign up to set email alerts
|

Anionic polymerization of 2,2,5,5‐tetramethyl‐1‐oxa‐2,5‐disilacyclopentane

Abstract: In the first of a two‐part series, a study has been made of the anionic polymerization of a five‐membered cyclocarbosiloxane, 2,2,5,5‐tetramethyl‐1‐oxa‐2,5‐disilacyclopentane. The polymerization was initiated by lithium n‐butyldiphenylsilanolate in the presence of tetrahydrofuran. The chemical shifts of the protons of the cyclic monomer and the polymer were found to be different, and therefore the rate of polymerization was obtained in an NMR spectrometer. The effects of varying the concentrations of THF, init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 7 publications
0
18
1
Order By: Relevance
“…We showed previously that ROP of neat monomer 2 is accompanied by a shrinkage of less than 5 %. [5] Likewise, ROP of 3 results in a similar loss of volume during the ROP reaction. Despite the structural similarity of 3 and 4, disilaoxacyclopentene 4, and the disilaindoles 5 and 6, [6] do not undergo ROP with a variety of anionic catalysts and reaction conditions.…”
Section: Phenylene-bridged Cyclic Siloxanes As Precursors To Nonshrinmentioning
confidence: 91%
See 2 more Smart Citations
“…We showed previously that ROP of neat monomer 2 is accompanied by a shrinkage of less than 5 %. [5] Likewise, ROP of 3 results in a similar loss of volume during the ROP reaction. Despite the structural similarity of 3 and 4, disilaoxacyclopentene 4, and the disilaindoles 5 and 6, [6] do not undergo ROP with a variety of anionic catalysts and reaction conditions.…”
Section: Phenylene-bridged Cyclic Siloxanes As Precursors To Nonshrinmentioning
confidence: 91%
“…[9] The dinuclear helicate A2 was formed in the presence of lithium, sodium, potassium as well as many other countercations. [10] For entropic reasons the formation of the dinuclear complexes A and B should be favored over the oligonuclear species C and D. [5] However, the binding of the countercations to the anionic coordination compounds either stabilizes the dinuclear complexes or destabilizes them leading to the formation of the oligomers C or D. [9,11] A red soluble solid is obtained when a 1:1 mixture of 1-H 4 and 2-H 4 with Ti(OMe) 4 (methanol, reflux or (acac) 2 TiO, methanol, room temperature) is treated with potassium carbonate as base and the solvent is removed. ).…”
Section: Phenylene-bridged Cyclic Siloxanes As Precursors To Nonshrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Piccoli et al first reported the anionic ROP of methyl-and/ or phenyl-substituted five-membered cyclocarbodisiloxanes and obtained high-molecular-weight polymers in 1960 [76]. Later investigations on the polymerization of these compounds have shown that this is a very efficient way to prepare poly(carbosiloxane)s of high molecular weight (M n = ∼130 000) and relatively narrow molecular weight distribution (M w /M n = 1.28-1.66) [77][78][79].…”
Section: Ring-opening Polymerization 231 Anionic or Cationic Ring-mentioning
confidence: 96%
“…On the other hand, relatively less attention has been paid to the synthesis of poly(carbosiloxane)s from cyclic carbodisiloxanes [76][77][78][79][80][81][82]. Piccoli et al first reported the anionic ROP of methyl-and/ or phenyl-substituted five-membered cyclocarbodisiloxanes and obtained high-molecular-weight polymers in 1960 [76].…”
Section: Ring-opening Polymerization 231 Anionic or Cationic Ring-mentioning
confidence: 99%